Diagnosis of the implementation of the RDA standard in the National Library System and State University Higher Education Library System - Briceño Alvarez, Iria (2024)
This research focuses on the implementation of the RDA cataloging standard in the National Library System (SINABI) and the State University Higher Education Library System (SIBESE) of Costa Rica. Using a qualitative and descriptive approach, which included literature reviews and surveys of key personnel from cataloging centers, the progress and challenges in the adoption of RDA were evaluated. The results show a notable commitment on the part of these institutions to update and adapt to new standards, despite limitations in technological and human resources. The implementation of RDA has made significant progress in training staff and updating cataloging policies, although it still faces challenges related to technological infrastructure and resistance to change. As libraries continue to modernize, full adoption of RDA is expected to significantly improve the quality of bibliographic description and information access in Costa Rican library systems. This diagnosis highlights the importance of a collaborative and adaptive approach in the implementation of international cataloging standards, adapting to the specific needs and available resources of each institution. It was concluded that the implementation of the RDA in Costa Rica is an evolving process, seeking to improve the quality of the bibliographic description and access to information.